Analysis of financial and non-financial aspects in determination of transfer pricing - Soap, Silva Fahsya Abdulrachman; Djati, Annisa Aulia; Grace, Vania Regina; Putri, Destiana Amelia; Huwaida, Najla; Wijaya, Suparna (Educoretax, 2024)
This research aims to analyze financial and non-financial aspects in determining transfer pricing. Transfer pricing is a crucial practice in the management of multinational companies as it directly impacts company profits, tax obligations, and relationships with investors. In transfer pricing practices, many companies misuse this method to manipulate prices for certain benefits. Transfer pricing practices occur due to various influencing factors. This research employs a descriptive analysis method using a literature review approach. A total of 30 previous studies from the period 2019 - 2024 were used as research samples, sourced from both national and international journals. Based on these previous studies, several variables were found to influence transfer pricing actions, observable from financial aspects such as profitability, taxes, and leverage, as well as non-financial aspects such as tunneling incentives, bonus mechanisms, and company size.